THE SYMBOLIC MEANING OF THE MENGKET RUMAH MBARU CEREMONY AMONG THE KARO ETHNIC GROUP - Br Tarigan, Dea Anisa; Jumiati Marsa, Yummy (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This study investigates the symbolic dimensions of the Mengket Rumah Mbaru ceremony, a traditional ritual deeply rooted in the cultural heritage of the Karo ethnic group. Despite its cultural richness, the practice of this ceremony has significantly declined, particularly in Kutabuluh Gugung Village, Kutabuluh Subdistrict, Karo Regency. This research stems from both an academic interest in the ceremony and a growing concern regarding the potential erosion of local traditions due to modernization and globalization. Employing a snowball sampling technique, data were collected through a gradually expanding network of informants. The analytical process involved four key stages: data collection, data reduction, presentation of findings, and drawing of conclusions. Data validity was ensured through triangulation, combining multiple sources, interviews, and direct observations conducted at various times of day. The findings suggest that Mengket Rumah Mbaru is not merely a ceremonial formality but a profound expression of the Karo people's identity, ancestral reverence, and cultural continuity. As such, preserving this tradition is vital to safeguarding the historical and spiritual legacy of the Karo community. Intergenerational transmission of this cultural practice is essential to ensure its survival in the face of contemporary challenges.Keywords: Symbolism, Mengket, Karo ethnicity, cultural heritage, tradition preservation